The Role of the Lateral Pterygoid Muscle in Articular Disc Displacement: A Cross-sectional Magnetic Resonance Imaging Study - Alqhtani, Nasser; Alshadwi, Ahmad A.; Al-Zahrani, Adel; Alshagroud, Rana Saud; Al Rafedah, Ali; Al Abdulsalam, Abdullatif; Almalki, Abdulrahman; Sakka, Salah (Current Medical Imaging, 2022)
Objective: The objective of the study is to determine the role of Lateral Pterygoid Muscle LPM in the articular disc displacement ADD, which is considered controversial due to the variations in the pattern of insertion of the Superior Lateral Pterygoid Muscle SPLM. Background: It is well understood that the superior head of the lateral pterygoid muscle has only a single insertion pattern among individuals, in which the muscle is attached to the articular disc and capsule. However, recent findings in many studies have shown a noticeable variation in the insertion pattern of the upper LPM. Methods: MRI examinations were collected at King Faisal Specialist Hospital & Research Centre, Riyadh, Saudi Arabia. Scans of 61 patients (41 females, 20 males; mean age 33 years old) with symptoms of temporomandibular dysfunction were reviewed retrospectively. The direction of their articular disc displacement was evaluated through sagittal and coronal views in both open and closed mouth positions. Results: There was no statistical significance found between the LPM attachment types and TMJ disc position. The chi-square test also showed no significant difference between the type of LPM attachment and the condylar location. Forty-five percent of the articular discs were located between the articular eminence and the glenoid fossa. The majority of the disc displacement was in the anterior direction. Conclusion: There was no statistically significant association found between the type of LPM attachments and the direction of disc displacement.
Keywords: temporomandibular joint